Pandemia de Covid-19 e saúde mental: vivências de familiares e pacientes internados durante a segunda onda no Ceará-Brasil - Muñoz Tello, Toa Leonor (2023)
The mental health of the global population is a topic of relevance in contemporary times. After all the changes and consequences that the pandemic has brought to the world, mental health problems have increased rapidly in recent years and have directly or indirectly affected society as a whole. Of course, there are specific groups that are at greater risk to their mental health than others; one of these are hospitalized patients with COVID-19 and their families, because they had a much more direct approach with this disease. For this reason, the present research aimed to understand the psychological processes of patients who were hospitalized with COVID-19 and their family members at the Walter Cantídio University Hospital, between March and June 2021. A qualitative methodological approach was used, with the interview semi-structured as a technique and with the interview script as an instrument, which was applied to sixteen patients who were hospitalized with COVID-19 and sixteen family members. Data were analyzed using Bardin's (2016) content analysis, identifying key elements of the study phenomenon through the thematic analysis technique.This research pointed to the understanding of psychological processes: it met the challenges experienced during hospitalization, which were greater when there was comorbidity, ICU admission or other family problems, also, psychological sequelae were identified in all respondents, the most common being insomnia, identified the processes of mourning and loss in those who experienced the death of a family member or close friend and presented psychological coping strategies, the most used being faith in God and support networks. Finally, it was evident that, after COVID19, this population values the importance of mental health in their lives, seeking psychological care, many of them for the first time in their lives. With this, it was also seen that mental health services, after large waves of the pandemic, had a very high demand, making it difficult to serve this population. It is concluded that understanding the psychological processes of this population is directly related to the severity of the disease and the context of the hospitalization experience, the person's previous health status and loss processes experienced, in addition to the adequate use of coping strategies. This research contributes and motivates the recognition, care and attention of mental health in the face of possible future scenarios of serious public health problems, so as not to leave isolated an aspect as relevant as the psychological processes of individuals directly involved with the current pandemic or other epidemics that can introduce themselves. Finally, subsidies are presented to increase actions regarding current psychosocial demands in the context of public health.